Effects of a Short Course of Inhaled Corticosteroids in Noneosinophilic Asthmatic Subjects. Issue 5 (2011) - Lemière, Catherine; Tremblay, Caroline; FitzGerald, Mark; Aaron, Shawn D; Leigh, Richard; Boulet, Louis-Philippe; Martin, James G; Nair, Parameswaran; Olivenstein, Ronald; Chaboillez, Simone
Abstract : BACKGROUND: Noneosinophilic asthma has been regarded as a distinct phenotype characterized by a poor response to inhaled corticosteroids (ICS). OBJECTIVE: To determine whether noneosinophilic, steroid-naive asthmatic subjects show an improvement in asthma control, asthma symptoms and spirometry after four weeks of treatment with ICS, and whether they further benefit from the addition of a long-acting beta-2 agonists to ICS. METHODS: A randomized, double-blind, placebo-controlled, multicentre study comparing the efficacy of placebo versus inhaled fluticasone propionate 250 μg twice daily for four weeks in mildly uncontrolled, steroid-naive asthmatic subjects with a sputum eosinophil count ≤2%. This was followed by an open-label, four-week treatment period with fluticasone propionate 250 μg/salmeterol 50 μg, twice daily for all subjects. RESULTS: After four weeks of double-blind treatment, there was a statistically significant and clinically relevant improvement in the mean (± SD) Asthma Control Questionnaire score in the ICS-treated group (n=6) (decrease of 1.0±0.5) compared with the placebo group (n=6) (decrease of 0.09±0.4) (P=0.008). Forced expiratory volume in 1 s declined in the placebo group (−0.2±0.2 L) and did not change in the ICS group (0.04±0.1 L) after four weeks of treatment (P=0.02). The open-label treatment with fluticasone propionate 250 μg/salmeterol 50 μg did not produce additional improvements in those who were previously treated for four weeks with inhaled fluticasone alone. CONCLUSION: A clinically important and statistically significant response to ICS was observed in mildly uncontrolled noneosinophilic asthmatic subjects.